PENGARUH KEAHLIAN TERHADAP KUALITAS AUDITOR PADA INSPEKTORAT KOTA PAREPARE - Anggara, Andi Rezky; Irwan, Irwan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect, namely: Does expertise affect the quality of auditors at the Inspectorate of Parepare City. Based on the problems mentioned above, the objectives to be achieved in this study are: To find out whether expertise affects the quality of auditors at the Parepare City Inspectorate. The data analysis method used in this research is simple linear regression analysis. The conclusions in this study are: The results of simple linear regression analysis show that the skill variable has a significance value of 0.001 so it can be declared significant because the significance value of the skill variable is smaller than the significance value of, which is 0.05. This shows that the independent variable expertise has a significant influence on audit quality at the Regional Inspectorate Office of Parepare City. The suggestions in this study are: In this research, there is input for the relevant agencies. And can increase the quality of auditors in handling supervision at the Parepare City Inspectorate. And it can be further improved performance or training to be certified in the quality of auditors. It is expected to add another independent variable so that it is likely to have a significant or measurable effect.